Faktor dan Dampak Pernikahan Usia Anak di Dusun Bentenu Desa Banyu Urip Kecamatan Gerung Kabupaten Lombok - Maswinda; M. Mabrur Haslan; Basariah (Mataram University, 2026)
This study aims to determine the various causes and impacts of child marriage in Bentenu Hamlet, Banyu Urip Village, Gerung District, West Lombok Regency. This study uses a qualitative approach with a phenomenological method with analysis as an approach to understand social phenomena from the perspective or experience of informants. The technique for determining informants in this study used a purposive sampling technique consisting of two married couples who had child marriages at the age of less than 20 years. Data collection techniques were carried out through interviews, observation, and documentation. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. Data validity was checked using source triangulation techniques, technical triangulation, and time triangulation. The results of the study indicate that there are several factors that encourage child marriage, namely individual factors, low levels of education, promiscuity, environmental conditions, as well as family economic factors and media factors. The impacts found include health aspects such as an increased risk of pregnancy and childbirth complications, economic aspects with weak financial conditions, and parenting aspects that indicate the unpreparedness of young couples in raising children. Thus, child marriage has significant negative impacts and requires attention and intervention from various parties. Keywords: Child Marriage, Causes, Impacts